Small and Medium Industry Data Report Input Application Design Using Kodular and Airtable - Akbar, Muhammad; Prahayu Ningsri, Prahayu Ningsri (Journal of Computer Science and Informatics Engineering, 2023)
The Department of Industry and Trade of North Sumatra still uses a manual system, especially in the functional sector in collecting data reports on Small and Medium Industries assisted by Field Extension Workers (IKM-TPL) in North Sumatra. The current manual system is very ineffective and inefficient in terms of time and finance, because each TPL from various regions must create and print data in the form of reports and then send it directly to DISPRINDAGSU. become more effective and efficient. The data collection technique used is by conducting observations and interviews. After doing the research, the writer implements the research results by building an application using Kodular and Airtable as the database. Besides being able to help employees work more accurately and efficiently, making this application is also part of an adjustment to the development of current technological advances. Keywords: Mobile Application, Kodular, Airtable